Adverse event reporting of four anti-Calcitonin gene-related peptide monoclonal antibodies for migraine prevention: a real-world study based on the FDA adverse event reporting system - Sun, Wenfang; Li, Yali; Xia, Binbin; Chen, Jing; Liu, Yang; Pang, Jingyao; Liu, Fang; Cheng, Hua (Frontiers in Pharmacology, 2024)
Background: Anti-Calcitonin gene-related peptide monoclonal antibodies (anti-CGRP mAbs) have shown significant efficacy in preventing migraine. However, there have been limited reports of adverse events (AEs) after marketing, particularly for eptinezumab launched in 2020. The study aimed to mine and analyze the AE signals with four anti-CGRP mAbs from the United States Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) database to gain insights into the safety profile of these medications post-marketing. Methods: All AE reports on the four anti-CGRP mAbs (erenumab, galcanezumab, fremanezumab, and eptinezumab) were retrieved from the FAERS database from the first quarter (Q1) of 2018 to Q1 of 2023. Disproportionality analysis was measured by reporting odd ratio (ROR) and Bayesian confidence propagation neural network (BCPNN) to identify potential AE signals. Comparisons were made between the four drugs in terms of AEs.Results: A total of 38,515 reports of erenumab, 19,485 reports of galcanezumab, 5,332 reports of fremanezumab, and 2460 reports of eptinezumab were obtained, mostly reported in the second to third year after launch in the market. The common AEs to erenumab included constipation (22.60%), injection site pain (14.08%), and alopecia (7.23%). The AEs that occurred more frequently with galcanezumab included injection site pain (24.37%), injection site erythema (5.35%), and injection site haemorrhage (4.97%). Common AEs related to fremanezumab were injection site pain (13.10%), injection site erythema (7.02%), and injection site pruritus (5.47%). Fatigue (13.54%), throat irritation (9.02%), and pruritus (8.20%) were the most common AEs with eptinezumab. In addition, there are new AEs that were not listed in the drug instructions but occurred concurrently with multiple drugs, such as Raynaud's reaction, weight increase, menstrual disorders, throat tightness, and paraesthesia oral.: Common AE signals of the four anti-CGRP mAbs and new AE signals were found to provide a reference for clinical drug selection in clinical practice.